Limits of the quota law in federal public universities - Hugo Augusto Vasconcelos Medeiros; Ruy de Deus e Mello Neto; Alfredo Macedo Gomes (Arizona State University, 2016)
The paper analyzes if the devices in Brazilian quota law are sufficient to guarantee the aims of the affirmative action, in order to promote democratic access to higher education through a fair redistribution of reserved spots. Firstly, we consider the racial self-declaration as a criterion to decide access to the quota; secondly, the technical difficulties and the possibility of competition inter and intragroup; thirdly, the difference between the percentages of blacks, pardos, indigenes (PPI) and low income students in general population, and the percentages of blacks, pardos, indigenes (PPI) and low income students in the socioeconomic strata used by quota law to define the reserved spots. The criteria for reserved spot distribution comprehend not only the obligation of study all the high school in a public institution, but also devices for calculus of the groups with access with reserved spots, according to four classifications: I-a: students from public middle schools, with per capita family income equal or less than 1,5 minimum wage, and PPI; I-b: students from public middle schools with per capita family income equal to or less than 1,5 minimum wage, no PPI; and II-a: students from public middle schools with per capita family income above 1,5 minimum wage, PPI; II-b: students from public middle schools with per capita family income above 1,5 minimum wage, no PPI. Metodologically, we analyzed documents related to the quota law process, and comparative quantitative analisys of the educational and demographical census is made. We conclude that despite its importance as a landmark to affirmative actions in higher education, quota law doesn't have the necessary conditions to guarantee a fair distribution of the reserved spots.